Crossroads—Reconsidering the “Fact-Value Antinomy: A Comment on Eastman and Bailey (1997)” - Connell, Ann F.; Nord, Walter R. (Organization Science, 1998)
Eastman and Bailey (this issue) positioned their paper as both an extension of and a challenge to Barley and Kunda (1992). In our view, it succeeds admirably as an extension: the two papers taken together benefit our field by calling attention both to the patters they reported and to the often neglected dynamics of the history of ideas in organization studies. However, we find Eastman and Bailey's challenge to Barley and Kunda, which entails the suggestion of an alternative hypothesis to theirs, to be less convincing. We begin by attempting to synthesize the two papers. Next, since one of Eastman and Bailey's purposes was to inspire other students of organizations to mediate the seeming conflict between “fact” and “value,” we make some remarks toward that end. These remarks reframe the conflict so that it makes more sense to us, question the purpose of mediating the conflict and suggest further steps toward integrating information from the history of ideas and dealing with the conflict Eastman and Bailey address.